Studies on the Production of Sorghum Vermicelli Supplemented with Defatted Soy Flour - - (Agriculture and Natural Resources, 1992)
Studies on the production of sorghum vermicelli supplemented with different levels of defatted soy flour indicated that the nutritive value of the products were markly improved. The protein content of the defatted soy bean flour supplemented sorghum vermicelli were 2-3 fold higher than that of the commercial vermicelli, i.e. 12.4%, 17.1% and 20.4% protein for 10%, 20% and 30% defatted soy bean flour supplemented sorghum vermicelli respectively. The protein quality is comparable to that of reference protein. The acceptability of the vermicelli was carried out by organoleptic test. The results obtained showed that all the samples tested were acceptable in all the parameters tested, i.e. color, flavor and texture. However, it was also found that the more the defatted soy flour supplemented, the higher the rehydration capacity, while the strength of the product was found decreased when the amount of defatted soy flour supplemented increased. In addition the shelflife of the products also found improved better than sorghum vermicelli supplemented with the full fat soy flour.